PENGARUH ARUS KAS TERHADAP LIKUIDITAS INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2009-2013 - Ari Wibowo, 11.05.52.0093; Lisiantara, G. Anggana (Students Journal of Accounting and Banking, 2015)
This study aims to examine and analyze the effect of the cash flow for the companys liquidity consumer goods industry listed in Indonesia Stock Exchange (IDX) 2009-2013.Â  The population in this study is a financial statement that the consumer goods industry companies listed in Indonesia Stock Exchange (IDX) from 2009 -2013. The sampling technique in this research is by using purposive sampeling. While the data analysis techniques used in this study is multiple regression analysis. The research proves that: Cash flows from operating activities a significant positive effect on liquidity. Cash flows from investing activities not significant negative effect on liquidity. Cash flows from financing activities is not significant negative effect on liquidity.Keywords: Operating Cash Flow, Investment Cash Flow, Cash Flow Funding and Liquidity